Students’ perception of learning vocabulary by using words of wonders applications - Sukma, Elsa Muliani; Lubis, Yani (Univeritas Papua, 2025)
Words of Wonders is a game-based crossword application that is believed to assist students in improving their vocabulary mastery. This research seeks to explore students' perceptions regarding the use of the Words of Wonders application in vocabulary learning. The study employs a mixed-method approach, utilizing observation, questionnaires, and interviews as data collection instruments. This study involved 30 students from a senior high school in Medan as questionnaire respondents and 10 students who participated in interviews. The result showed the students have positive perceptions, namely: Words of Wonders is adjustable, vocabulary expansion, interactive learning, and enhances critical thinking skills by connecting random letters into cohesive words. The findings highlight the alignment between questionnaire and interview results, reflecting favorable student perceptions. Consequently, Words of Wonders is recommended as an effective vocabulary learning tool. Nevertheless, further studies involving a larger number of participants are necessary to gain more comprehensive insights into students' perceptions and to evaluate the strengths and weaknesses of the Words of Wonders application in vocabulary learning.